Аналіз факторів техногенного впливу на кліматичні зміни в Україні - Недава, О.А. (Проблемы машиностроения, 2017)
Обґрунтовується висновок, що найважливішою складовою глобальних кліматичних змін на Землі, в тому числі сучасного потепління, є антропогенна діяльність, що характеризується неефективним використанням природних ресурсів, а також гранично небезпечним рівнем забруднення навколишнього середовища. Показано кореляцію обсягів викидів парникових газів техногенного походження зі збільшенням середньорічної температури. Обосновывается вывод, что важнейшей составляющей глобальных климатических изменений на Земле, в том числе современного потепления является антропогенная деятельность, характеризующаяся неэффективным использованием природных ресурсов, а также – предельно опасным уровнем загрязнения окружающей среды. Показано корреляцию объемов выбросов парниковых газов техногенного происхождения с увеличением среднегодовой температуры. The article substantiates the finding that the key component contributing to global crises on Earth, including current warming, is the economic (predatory and hyper-consumption) activity of the ever-increasing human population, including the significant growth in inefficient use of natural resources, as well as the extremely hazardous environmental pollution by supertoxicants. All this has led to suppression, degradation, destruction and annihilation of ecosphere systems, changes in the global flow of carbon and oxygen, reduction of carbon dioxide drain and accumulation of greenhouse gases in the troposphere and, as a consequence, to global warming. The technique of determining the reserves of energy and resources on the basis of the integral ion model of functioning of territorial-industrial complexes is considered in the article. The main aim of the work is to develop the methods of integration of energy and material flows enterprises located in territorial and industrial zones, providing rational use of all kinds of resources, reduction of waste and anthropogenic impact on the environment. One way to achieve this aim is a methodology hased on intersectoral integration energetic and technological industrial potential, which can be combined in the framework of territorial and industrial complexes. It is proposed a mathematical model for the analysis of reserves of energy and resources in the implementation of technological integration plants located within the territorial and industrial zones, as well as analysis of consumption of resources and waste generation of enterprises. The results can be applied to the fuel and energy complex, machine building enterprises, mining and metallurgical and chemical-technological profile. The proposed technique makes it possible to realize in practice low-waste energy efficiency production for the development of territorial and industrial complexes, provides a reduction in the unit cost of energy and raw materials in 2,2–3,5 times with simultaneous reduction in emissions by 2–3 Limes.